HOGARES DE LA FRONTERA NORTE DE MÉXICO. CAMBIOS SOCIO-DEMOGRÁFICOS EN EL MARCO FAMILIAR TRADICIONAL / HOMES OF THE NORTHERN BORDER OF MEXICO. SOCIODEMOGRAPHIC CHANGES IN THE TRADITIONAL FAMILY SETTING - Humberto González Galbán; Adriana Ortiz Peredo (Barataria, 2017)
Commonly arises in the literature that in the context of the family institution operates daily, generational and social reproduction of the population, which however is controversial at present both the diversity of existing types of families as the transformations that they are experiencing. It deserves to be duly evidenced in interaction with the existing environment and sized according to the importance attributed to this social organization. For the investigation of the aspects indicated in the present article, we analyze indicators that emphasize basically the young people of the northern border of Mexico and the familiar problems around them. The results show a higher proportion of non-nuclear households where young people live than in the rest of the country. It is also remarkable a greater sexual activity outside of stable unions without counting these with previous preparation for it.